The Potential Increase of Household Consumption Through Online Shopping as East Java Economic Growth Acceleration Effort in The Covid-19 Pandemic: Optimization of Social Demographic and Spatial Factors - Taly Purwa; Yusi Krismaningtyas (East Java Economic Journal, 2021)
The economic shock as a result of the Covid-19 pandemic resulted in an economic contraction, including East Java. The shift in consumer behavior in utilizing e-commerce to adapt to pandemic constraints is a good catalyst for stimulating household final consumption as the largest shareholder in the East Java economy. This study tries to identify socio-demo graphic and spatial factors that can be optimized for the acceleration of East Java’s eco nomic growth during the disruption from the demand side. The results of the identification of individual behavior in online shopping as well as district/city aggregates indicate several socio-demographic and spatial factors that can be optimized. Mapping districts/cities based on the dimensions of online shopping activities and ICT infrastructure conditions can be a more specific alternative solution to further optimize the potential for increasing household consumption as an effort to accelerate economic growth during the Covid-19 pandemic appropriate with the characteristics of each region.